Tumor immunomodulatory effects of polyphenols - Wang, Qin; Yang, Bin; Wang, Nan; Gu, Jian (Frontiers in Immunology, 2022)
Polyphenols, commonly found in various plants, have attracted enormous attention due to their potential pharmacological activity, especially antitumor activity dependent on immune function. In recent years, the development of nanomedicine can counteract the low bioavailability of polyphenols and improve the effect of tumor treatment. Among them, metal-phenolic networks (MPNs), which utilize various metal ions and phenolic ligands for coordination binding, have now become candidates for polyphenol-based nanomedicine treatment of tumors. In this mini-review, we described the classification of polyphenols and their mechanisms in antitumor immune responses, and provided suggestions for the next steps of treating tumors with polyphenols.